Tinjauan Sistematis Faktor Lingkungan dan Perilaku terhadap Keracunan Timbal pada Anak - Hardiansyah, Ali (Journal of Medical and Health Sciences, 2025)
Lead poisoning in children remains a global environmental health issue with serious impacts on physical, cognitive, and behavioral development. This study aims to systematically review environmental and behavioral factors associated with lead poisoning in children. The research method employs a systematic review approach based on PRISMA guidelines. Literature was searched through databases including PubMed, Scopus, ScienceDirect, and Google Scholar, covering publications from 2013 to 2023. Selected articles were observational studies focusing on children and reporting risk factors for lead poisoning. Selection, data extraction, and quality assessment were conducted independently by two researchers using the Joanna Briggs Institute (JBI) Critical Appraisal Tools. The review found that environmental factors such as air pollution from motor vehicles, the use of lead-based paint, and contamination of water and soil from industrial waste are major contributors to lead exposure in children. Additionally, behavioral factors such as hand-to-mouth activity, poor personal hygiene, and malnutrition increase the risk of lead absorption. Socioeconomic factors, including parental education and household income, also influence vulnerability levels. The findings indicate that children living in industrial and high-traffic urban areas are at higher risk compared to those in non-industrial regions. The conclusion of this review emphasizes the need for comprehensive preventive efforts through pollution source control, improved health education, and nutritional interventions. Multisectoral strategies involving government, healthcare professionals, and the community are essential to protect children from the harmful effects of lead poisoning.